PENERAPAN THEORY OF CONSTRAINTS (TOC) UNTUK MENINGKATKAN KINERJA PRODUKSI DI INDUSTRI MANUFAKTUR - Ruhimat, Agus (Journal Industrial Manufacturing, 2025)
This research aims to identify and overcome the main obstacles in the production process of LED Classic lamps at PT. Berdikari Inti Gemilang by using the Theory of Constraints approach. The main problem faced by the company is the low production output due to limited capacity at certain workstations. The methods used in this study include bottleneck identification, capacity analysis, and the implementation of Drum-Buffer-Rope to optimize production flow. The results showed that the installation workstation SK-3 was the most significant bottleneck in the production flow. After analysis and improvements, such as adding buffers, standardizing work, and increasing operator work effectiveness, there was an increase in production output and a decrease in the defect rate. The overall implementation of Theory of Constraints has been proven to be able to improve production performance without the need for large investments in machinery or labor.Keywords: Theory of Constraints, Drum-Buffer-Rope, bottleneck, LED production, efficiency.